Examen especial a la cuenta de inventarios de fármacos e insumos médicos de la Dirección Distrital de Salud nº 23d02 del cantón Santo Domingo en el período comprendido del 01 de enero al 31 de diciembre del 2014 - Gavidia Meneses, Sofia Enith (2015)
This research had as main objective to carry out a special examination to the inventory account of drugs and medical supplies of the District Health Department No. 23D02 in the period from January 1 to December 31, 2014, prior to obtaining Title of Certified Public Accountant, was executed by applying the Internal Control Standards and Handbooks Ministry of Health, in order that the established procedures allow us to obtain sufficient evidence, competent and documentaries from the findings presented. It began with the proper authorizations from the authorities of the District Health Department No. 23D02 for this special review, questionnaires were applied cellar observations, interviews and notes of the most relevant were performed; District Address information was gathered and proceeded to meet in general procedures related to inventories of drugs and medical supplies. The techniques that were used in this research were: the interview that allowed us to get more information about the processes and shortcomings of the institution, the observation that helped visualize the different activities, processes and functions of the staff, the questionnaire He used for insight into specific points of the institution, and lastly the documentary research provided with documentary information that served to support this work. People who applied surveys were: district, financial and administrative, warehouse manager and director in charge of acquisitions. The results demonstrate that taking the physical inventory is occasionally performed without determination of time. Receipt and storage of drugs and medical supplies they are not done with the appropriate security measures for their conservation and maintenance. This special consideration to the inventory account of drugs and medical supplies was feasible because it had a positive impact by improving inventory control with a high level of efficiency and effectiveness in the development of their activities.